Association Between the Apolipoprotein E Gene Polymorphism and Atherosclerotic Middle Cerebral Artery Stenosis. Issue 2 (March 2018) - Zhang, Zhengsheng; Chen, Xiang-yan; Baum, Larry; Ng, Ho Keung; Mok, Vincent; Wong, Ka Sing
Abstract : Objectives: Stenosis of the intracranial large arteries, especially the middle cerebral artery (MCA), is common in the Chinese population. We conducted a case-control study to investigate clinical and apolipoprotein E (ApoE) gene polymorphism of MCA atherosclerosis in the Chinese population. Materials and Methods: Polymerase chain reaction–based protocols were used to identify the genotypes of polymorphisms in ApoE genes. Clinical parameters and the genotypes of polymorphisms in the ApoE genes were compared in patients with and without MCA stenosis. The ApoE exon ε4 genotypes with risk factors were compared in the patients with and without MCA stenosis. Results: In total, 337 ischemic stroke patients were recruited, 156 cases with and 181 without MCA stenosis. Univariate analysis showed that the levels of systolic blood pressure and pulse pressure were higher in the MCA-stenosis group. There were no significant differences in the genotype and allele frequencies of the ApoE polymorphism observed between patients with and without MCA stenosis. However, there was a trend that the MCA-stenosis group tended to have more of genotype ε4/ε4 (3.8% vs. 0.6%, P =0.052) than the non–MCA-stenosis group. There was no effect of ApoE genotype and genotype-by-environment interactions on ischemic stroke susceptibility. Conclusions: This present study indicated that the hypertension (ie, systolic blood pressure and pulse pressure) and the ApoE ε4/ε4 genotype may be associated with the occurrence of MCA stenosis in the ischemic stroke Chinese patients.